PERTUMBUHAN BIBIT POLIEMBRIONI JERUK SIAM (Citrus nobilis Lour.) ASAL KAMPAR - Widianti '; Dyah Iriani; Fitmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Siam orange (Citrus nobilis Lour.) from Kampar has a polyembryonic seed, thephenomenon of development of more than one embryo in a seed. One embryo derivedfrom the fusion of two gametes (sexual) and the other derived from nucellar cells(asexual). Polyembryonic seeds will produce apomictic seedlings that have resistance topests and diseases with a better root system that can improve the needs of seeds in citruspropagation of siam orange from Kampar. The aims of this study were to investigate thecharacteristics of poliembryonic seedlings and also to calculate the percentage ofpolyembryonic seedlings. Data was quantitatively analyzed by calculating thepercentage of polyembryonic and germination seedlings. The results showed that thepercentage of the germination seeds was 43.75% and the polyembryonic seeds was68.4% which consisted of two to three seedlings.